Impact of Crude Oil Price on Countries’ and Vietnam’s GDP Growth: Variance Decomposition Approach - Dinh, Doan Van (International Journal of Energy Economics and Policy, 2021)
The crude oil price fluctuation investigation is to explore the impact of crude oil price shocks on the countries’ economic growth. The Vector Autoregressive Model (VAR) was applied and the variance decomposition is to analyze the impact of the GDP growth due to the shock of the crude oil price. Besides, nine countries’ data were collected from 1990 to the third quarter of 2020. The countries’ GDP growth was impacted by the crude oil price in 5 years respectively: 44.98%; 40.03%; 31.06%; 32.27%; 33.21%; 36.03%; 27.79%; 15.35%; 40.75% of the following countries are: China; America; Japan; Korea; Singapore; Thailand; Indonesia; Vietnam; Malaysia. This study identifies issues for countries to consider: have a comprehensive solution among macroeconomic policies, monetary policy, fiscal policy and other policies to control and stimulate growth. Keywords: Impulse response functions, Oil price stabilization fund, economic growth, cointegration method, macroeconomic policies. JEL Classifications: E31, E37, D24 DOI: https://doi.org/10.32479/ijeep.10852